2022
DOI: 10.1007/s10924-022-02704-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hemocompatibility of Lysine Grafted Polyacrylonitrile Electrospun Nanofiber Membranes as a Potential Bilirubin Adsorption in Hemoperfusion

Abstract: Hyperbilirubinemia is one of most severe clinical diseases, which is caused by the accumulation of unconjugated bilirubin. Electrospun nanofiber membranes used as highly efficient bilirubin adsorbents have been applied to remove the extra bilirubin in hemoperfusion for their high surface area and easy functionalized properties. In this work, Lysine (Lys) grafted polyacrylonitrile (PAN) electrospun nanofiber membranes doped with organic Hectorite (OHec) (Lys-HPAN@OHec) have been fabricated via a series of modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Liu and co-workers grafted lysine on polyacrylonitrile electrospun nanofibers. The maximum adsorption capacity toward bilirubin was 64.0 mg g −1 [ 16 ]. Studies have found that necessary modifications need to be carried out on electrospun fibers before their usage as bilirubin adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and co-workers grafted lysine on polyacrylonitrile electrospun nanofibers. The maximum adsorption capacity toward bilirubin was 64.0 mg g −1 [ 16 ]. Studies have found that necessary modifications need to be carried out on electrospun fibers before their usage as bilirubin adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis has a poor removal effect on albumin bound bilirubin, and HP is the most effective method for treating hyperbilirubinemia. 6,7…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis has a poor removal effect on albumin bound bilirubin, and HP is the most effective method for treating hyperbilirubinemia. 6,7 The adsorbent in the HP column determines the effectiveness of bilirubin removal, so the development of safe and efficient bilirubin adsorbents is of great signicance. 8 Traditional bilirubin adsorbents such as activated carbon, 9 adsorption resin, 10 polymer beads 11 and bilirubin imprinted polymers 12 and novel bilirubin adsorbents based on nanomaterials including aerogels, 13,14 MOFs, 15,16 nanober materials, 3,17 MXene 18,19 have been continuously reported and innovated for many years to improve adsorption efficiency.…”
Section: Introductionmentioning
confidence: 99%